Heavy Metal (Pb, Cu, and Zn) Content in Geloina erosa and Cerithidea obtusa from the Western Coast of Dumai, Riau Province - Fajriani, Annisa; Amin, Bintal; Efriyeldi, Efriyeldi (Journal of Coastal and Ocean Sciences, 2025)
Industrial and shipping activities in coastal areas have the potential to increase heavy metal pollution, which can accumulate in marine organisms and impact food safety. On the west coast of Dumai, Geloina erosa and Cerithidea obtusa are widely consumed by the local community, making it important to study their heavy metal content. This study aims to analyse the levels of Pb, Cu, and Zn in the soft tissues of these two species and compare the differences between species and sampling locations. The study was conducted in February 2025 at two stations: Station 1 (Purnama) and Station 2 (Pangkalan Sesai). Samples were collected using purposive sampling and analysed using Atomic Absorption Spectroscopy (AAS). The results showed that the average Pb, Cu, and Zn content in G. erosa were 6.79 µg/g, 6.13 µg/g, and 8.36 µg/g, respectively, while in C. obtusa they were 7.09 µg/g, 6.27 µg/g, and 7.41 µg/g. Significant differences (p < 0.05) were detected in the Cu and Zn content in G. erosa, as well as Zn in C. obtusa, between stations. Pb and Cu were generally higher in both species at Station 2, while the highest Zn levels were found in G. erosa at Station 1 (9.12 µg/g) and C. obtusa at Station 2 (8.50 µg/g). The highest PTWI value was found in G. erosa at Station 1; however, all results remained within safe consumption limits. Therefore, both species are deemed safe for consumption, despite variations in heavy metal content between species and research locations